Lymphocytic Interstitial Pneumonia and Other Benign Lymphoid Disorders - Tian, Xinlun; Yi, Eunhee S.; Ryu, Jay H. (Seminars in Respiratory and Critical Care Medicine, 2012)
Nonneoplastic pulmonary lymphoid disorders consist of a complex spectrum of diseases for pathologists and pulmonologists alike. Advances in our understanding of these disorders in recent years have led to revisions in the classification scheme. This review summarizes the clinicoradiological and pathological features of several benign pulmonary lymphoid disorders as well as the current knowledge regarding their pathogenesis. The disorders discussed include lymphocytic interstitial pneumonitis, follicular bronchiolitis, nodular lymphoid hyperplasia, inflammatory pseudotumor, Castleman disease, immunoglobulin G4–related disease in the lung, and posttransplant lymphoproliferative disease.
Keywords: lymphocytic interstitial pneumonia; pulmonary lymphoid disorders; pseudolymphoma